2011
DOI: 10.1297/cpe.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance during Puberty in Non-obese Japanese Children

Abstract: We examined whether non-obese Japanese children without diabetes exhibited insulin resistance during puberty. The study subjects were 201 Japanese school students, consisting 95 males and 106 females, aged 11.5 ± 2.6 yr. None of the subjects were obese, with the mean percent of overweight being 0.7 ± 10.5%, or had diabetes at the time of the study. Overnight fasting plasma values of insulin (FIRI) and HOMA-R were measured, with concomitant measurement of the plasma glucose (FPG) levels. The mean FPG, FIRI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…However, we also found that nonobese patients showed significantly higher insulin resistance as compared with age- and pubertal stage-matched Japanese people without diabetes in other studies ( Fig. 4 ) [ 16 , 17 ]. Accordingly, nonobese patients show lower insulin secretion abilities, but have milder, but evident, insulin resistance even from the time of diagnosis.…”
Section: Clinical Characteristics In Japanese Children With Nonobese supporting
confidence: 75%
“…However, we also found that nonobese patients showed significantly higher insulin resistance as compared with age- and pubertal stage-matched Japanese people without diabetes in other studies ( Fig. 4 ) [ 16 , 17 ]. Accordingly, nonobese patients show lower insulin secretion abilities, but have milder, but evident, insulin resistance even from the time of diagnosis.…”
Section: Clinical Characteristics In Japanese Children With Nonobese supporting
confidence: 75%
“…The mean FIRI and HOMA‐R in normal children were 9.0 ± 3.6 µU/mL and 2.0 ± 0.9, respectively 9 . In contrast, these were significantly higher in all the patient groups, even in the non‐obese group A, than in normal children ( P < 0.01, respectively).…”
Section: Resultsmentioning
confidence: 83%